2010
DOI: 10.1177/0093854809357420
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction Among Psychologists Working in State Prisons

Abstract: There is growing demand for psychologists to work in correctional settings, and high vacancy rates indicate that efforts are needed to attract and retain employees. Job satisfaction has been associated with a variety of work-related outcomes such as productivity and turnover. In this study, 73 master’s- and doctoral-level psychologists working in one state prison system responded to a job satisfaction survey based on one developed by Boothby and Clements (2002). Respondents rated their overall job satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…prisons, MacKain, Myers, Ostapiej, and Newman (2010), found that three broad domains generated from a principle components analysis of Boothby and Clements' survey (economics, perceived organisational support, and interpersonal relationships) all significantly predicted overall job satisfaction. Similar to the findings of Boothby and Clements (2002), MacKain et al (2010) found that job security, relationships with clients, relationships with coworkers, and safety were rated as the most positive and satisfying whereas opportunities for advancement, salary, recognition, and ability to influence decision making were rated as the least satisfying and most negative.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…prisons, MacKain, Myers, Ostapiej, and Newman (2010), found that three broad domains generated from a principle components analysis of Boothby and Clements' survey (economics, perceived organisational support, and interpersonal relationships) all significantly predicted overall job satisfaction. Similar to the findings of Boothby and Clements (2002), MacKain et al (2010) found that job security, relationships with clients, relationships with coworkers, and safety were rated as the most positive and satisfying whereas opportunities for advancement, salary, recognition, and ability to influence decision making were rated as the least satisfying and most negative.…”
supporting
confidence: 70%
“…For instance, according to the 2009 Report of the Market Supplement Review Committee (Health Sciences Association of Saskatchewan, 2009), psychologist positions in the Alberta health regions start at $40.12 per hour (i.e., approximately $82,000 per year based on a 37.5 hr work week) and peak at $53.28 per hour (i.e., approximately $104,000), and the rates are generally comparable among the health authorities in BC and Saskatchewan. In the MacKain et al (2010) survey, salary received the second lowest satisfaction rating out of 18 items, although in the Boothby and Clements (2002) survey, it had a considerably higher satisfaction rating as the 10th highest item rated out of the 18.…”
Section: Clinical Training and Issues Of Recruitment And Retentionmentioning
confidence: 97%
“…Participants were prompted to indicate their agreement or disagreement with this statement on a 5-point Likert scale ranging from ''completely disagree'' to ''completely agree''. Although singleitem measures are discussed controversially, there is ample evidence that single-item measures of job satisfaction are sufficiently reliable (e.g., Dolbier, Webster, McCalister, Mallon, & Steinhardt, 2005;MacKain, Myers, Ostapiej, & Newman, 2010;Nagy, 2002;Scarpello & Campbell, 1983) including metaanalytical evidence (Wanous, Reichers, & Hudy, 1997), which additionally showed consistent reliability estimates across different single-item measures of job satisfaction. Thus, it can be assumed that reliability evidence of these studies generalizes to the present sample.…”
Section: Procedures and Measuresmentioning
confidence: 99%
“…(1) Organizational factors e.g., workrelated factors tasks and their importance, job title, independence, etc., and the promotion and reward system, leadership, training, relationships, working conditions, management, organizational commitment, organizational support, organizational learning. ( 2) Environmental factors such as public image and frustration with regulations and laws (Abdulla et al, 2011;Mackain et al, 2010). "Salary and incentive" was considered the strongest determinant of staff satisfaction compared with demographic factors and could be a source of satisfaction for staff.…”
Section: Staff Motivation and Satisfaction Precedents: Empirical Stud...mentioning
confidence: 99%
“…"Salary and incentive" was considered the strongest determinant of staff satisfaction compared with demographic factors and could be a source of satisfaction for staff. (Mackain et al, 2010;Nina Tomazevic et al, 2014). It has been suggested that, for many policemen, aspects of the organization and the context of the work contribute more to the sense of stress because policemen should deal with these pressures regularly if not daily.…”
Section: Staff Motivation and Satisfaction Precedents: Empirical Stud...mentioning
confidence: 99%